Levels of blood pressure, cardiovascular biomarkers and their correlations in women with previous pre-eclamptic pregnancy within 7 years postpartum: a cross-sectional study in Thailand - Tippawan Liabsuetrakul; Annetine Staff; Jarawee Sukmanee; Penkae Rothmanee; Wilaiwan Sriwimol (BMJ Open)
Objective To assess the levels of blood pressure, cardiovascular biomarkers and their correlations measured within 7 years postpartum in women with previous pre-eclamptic pregnancies compared with women with previous normotensive pregnancies.Design Cross-sectional study.Setting Two tertiary hospitals in the southern region of Thailand.Participants Women with pre-eclamptic and normotensive pregnancies in the past 7 years were enrolled from 1 October 2019 to 30 April 2021. Eligible women were interviewed, examined for body mass index (BMI) and blood pressure, and donated morning spot urine and blood samples.Primary outcome measures Serum high-sensitivity C reactive protein, creatinine, fasting blood glucose (FBS), glycated haemoglobin (HbA1c), low-density lipoprotein (LDL) cholesterol, urine microalbumin to creatinine ratio (UACR) and sodium were measured. Group differences in biomarkers were tested using unpaired t-test, Wilcoxon rank-sum test or χ2 test. The levels of blood pressure and biomarkers between the two study groups at <2 years, 2–4 years and >4 years were also compared. The correlations between blood pressure and biomarkers were analysed using Pearson’s correlation and partial correlation methods.Results From 206 women included in the analysis, 88 had pre-eclamptic pregnancies and 118 had normotensive pregnancies. Compared with women with previous normotensive pregnancies, women with previous pre-eclamptic pregnancies had significantly increased rates of hypertension (31.8% vs 7.6%, p<0.001) and obesity (55.7% vs 40.7%, p=0.038), as well as higher serum levels of FBS (p<0.001), HbA1c (p<0.001), LDL cholesterol (p=0.03), creatinine (p<0.001) and UACR (p<0.001). Correlation coefficients of BMI, serum creatinine and UACR with blood pressure ranged from 0.27 to 0.31.Conclusion The risk of hypertension after a pre-eclamptic pregnancy increased. Blood pressure measurement combined with BMI, serum creatinine and UACR screening at least once during 7 years postpartum is suggested for early detection of cardiovascular risk.